Systemic Condition, Periodontal Status, and Quality of Life in Obese Women During Pregnancy and After Delivery - Gerson Aparecido Foratori-Junior; Alana Luiza Trenhago Missio; Eliel Soares Orenha; Silvia Helena de Carvalho Sales-Peres (Elsevier, 2021)
Objective: To evaluate the systemic condition, periodontal status, and quality of life of obese women during pregnancy and after delivery. Methods: This prospective cohort consisted of 60 women examined in the third trimester of pregnancy (32nd-36th gestational week [T1]) and after delivery (T2) and were divided into elevated body mass index (BMI; GO = 30) and normal BMI (GN = 30) according to the World Health Organization. The variables assessed were: (1) gestational weight gain, arterial hypertension (AH), and diabetes mellitus; (2) oral hygiene behaviour (frequency of dental floss using and toothbrushing); (3) probing pocket depth (PPD), clinical attachment loss (CAL), bleeding on probing (BOP), and dental biofilm; and (4) quality of life (Oral Health Impact Project [OHIP]-14). Analysis of variance (ANOVA), Friedman, Cochran's Q and χ2 tests, and logistic regression model were adopted (P < .05). Results: GO showed a higher frequency of AH in T1 (P < .001). Both groups decreased the frequency of dental floss use (P = .013) and toothbrushing (P < .001) and increased the percentage of dental biofilm in T2 (P < .001). GO presented a greater PPD and CAL in T1 and T2 and higher BOP in T1 (P < .001), demonstrating a negative impact in the following dimensions of Oral Health Impact Project-14 during T1 functional limitation (P = .020), physical disability (P = .020), and handicap (P = .021). Conclusion: Obese women presented higher prevalence of AH during pregnancy and higher prevalence of periodontitis in both periods. They showed a poor quality of life in T1 regarding functional limitation, physical disability, and handicap.